2019
DOI: 10.1002/pat.4801
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized ZrP nanosheet with free‐radical quenching capability and its synergism in intumescent flame‐retardant polypropylene

Abstract: The combination of catalyzing carbonization and free-radical quenching mechanism is proposed to be a promising strategy for the preparation of high-efficiency flameretardant polypropylene (PP). Herein, a novel functionalized zirconium phosphate (RQZrP) nanosheet with free-radical quenching capability was fabricated by decorating macromolecular N-alkoxy hindered amine (MNOR) onto the surface of ZrP. It was combined with an intumescent flame retardant (IFR) to flame-retard PP. The results showed that there was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 36 publications
(36 reference statements)
0
14
0
Order By: Relevance
“…The absorption peaks at 592 and 521 cm −1 were assigned to Zr–O. The main characteristic peaks of RQMIFR exhibited the N–H stretching vibration peak at 3410 cm −1 , the –CH 2 – stretching vibration peak at 2930 cm −1 , and the triazine ring stretching and bending vibration peaks at 1580 and 801 cm −1 29 . For RQMIFR‐ZrP, it displayed the characteristic peaks of both ZrP and RQMIFR, which further proved the successful synthesis of RQMIFR‐ZrP.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The absorption peaks at 592 and 521 cm −1 were assigned to Zr–O. The main characteristic peaks of RQMIFR exhibited the N–H stretching vibration peak at 3410 cm −1 , the –CH 2 – stretching vibration peak at 2930 cm −1 , and the triazine ring stretching and bending vibration peaks at 1580 and 801 cm −1 29 . For RQMIFR‐ZrP, it displayed the characteristic peaks of both ZrP and RQMIFR, which further proved the successful synthesis of RQMIFR‐ZrP.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, free‐radical scavengers such as fullerene (C 60 ) 24,25 and hindered amine 26–28 were proved to be good synergists in improving the flame retardancy of IFR. Our previous works 29–31 revealed that a very small amount of N ‐alkoxy hindered amines (NOR) efficiently improved the flame retardancy of PP by free‐radical quenching. During the combustion, nitroxyl radicals (NO•) were generated from NOR and effectively quenched peroxy radicals (ROO•) to inhibit the degradation of PP.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to DOPO, other fire retardants with lower oxidation state P also possess a similar gaseous-phase free radical capture effect. For instance, Lai et al 106 reported a functionalized ZrP nanosheet (RQZrP) with a free-radical quenching capability, which shows improved flame retardancy for PP when combined with the IFR. Similarly, Xing et al 107 constructed an ionic liquid (IL) modified black phosphorus (BP) nanosheet (IL-BP) by self-assembly for flame retardancy of PU, and the final PU nanocomposite containing 2 wt% IL-BP achieved 38% and 20% reductions in PHRR and THR, respectively, as well as a 18 • C increase in the T onset compared with pure PU.…”
Section: Organophosphorusmentioning
confidence: 99%
“…Excess hindered amine would promote the thermal decomposition of PP, and accelerated its molten droplets, thus limiting the further improvement of its flame-retardant efficiency. 25 Therefore, how to effectively regulate the N-alkoxy-hindered amine content in MIFR is a key factor to realize the high efficiency of intumescent flameretardant PP.…”
Section: Introductionmentioning
confidence: 99%
“…This was mainly because the nitroxyl radical (NO•) generated by RQMIFR quenched the active freeradicals produced by the pyrolysis of PP in gas phase and inhabited the β-degradation of PP. In condensed phase, NO• captured the PP macromolecular free radicals and cross-linked with RQMIFR skeleton under the catalysis of inorganic acids to form a dense char layer, which effectively prevented the degradation and combustion of PP 25. Cone calorimeter test (CCT) was also employed to investigate the large-scale combustion behaviors of flame-retardant PP.…”
mentioning
confidence: 99%